Pelatihan Time Management Pada Ikatan Keluarga Mahasiswa (IKM) di STIKES Panti Waluyo Malang - Firlia Candra Kartika; Ratih Agustin Rachmaningrum; Richo Surya Pradana (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
This study aims to evaluate the effect of a time management training program on students, especially members of the Student Family Association (IKM) of STIKES Panti Waluya Malang. Using a quasi-experimental method with pre-test and post-test, this study collected data through focus-group-discussion and documentation. The training program designed based on the Training Need Assessment (TNA) results included lectures, discussions, case studies, roleplay, and ice-breaking. The results showed that the training was effective in improving participants' time management skills, with an increase in post-test scores between 10-35%, although there were barriers to participation due to busy schedules. The training helped students manage time between academic and organizational activities, which contributed to improved academic performance.